Efficacy and safety of intravenous tenecteplase thrombolysis in diffusion-weighted imaging-negative posterior circulation ischemic stroke - Zhang, Ying; Fu, Shengqi; Hu, Shengjie; Zhu, Lili; Li, Jiarong; Shi, Baoyang; Song, Liang; Yang, Dongdong (Frontiers in Neurology, 2025)
IntroductionClear evidence supporting thrombolytic therapy in diffusion-weighted imaging (DWI)-negative posterior circulation ischemic stroke (PCIS) is lacking. We aimed to investigate the efficacy and safety of intravenous thrombolysis using tenecteplase (TNK) for the treatment of DWI-negative PCIS.MethodA retrospective analysis was conducted on 310 patients with DWI-negative PCIS (TNK group, 100 patients; control group, 210 patients) with propensity score matching (PSM, 63 pairs). Efficacy was assessed using the 90-day modified Rankin Scale (mRS) score and early neurological deterioration (END); safety was evaluated by mortality and symptomatic intracerebral hemorrhage (sICH).ResultsThe PSM-matched cohort comprised 126 patients (67 men), with a mean age of 68.9 ± 7.9 years. After PSM matching, the 24 h National Institutes of Health Stroke Scale (NIHSS) scores of the two patient groups [3.0 (3.0, 5.0) vs. 4.0 (3.0, 6.0) points] and the NIHSS scores at discharge [2.0 (1.0, 3.0) vs. 3.0 (2.0, 4.0) points] (p < 0.05) were compared. In the PSM-matched TNK group, the 90-day 0–1 mRS score (85.7% vs. 58.7%, p = 0.028) and END rate (1.6% vs. 19.0%, p = 0.011) were significantly better than those of the control group with no increased mortality or sICH. However, the control group had a 90-day mortality rate of 3.2% (2/63; both patients died of stroke-induced pulmonary infections).ConclusionIn patients with DWI-negative PCIS, TNK increased the proportion of patients achieving a mRS score of 0–1, reduced the incidence of END, improved long-term prognosis, and demonstrated a favorable safety profile; in contrast, the control group exhibited a higher incidence of END and poorer overall prognosis. Notably, this study has limitations, including its single-center retrospective design and small sample size after PSM, which may restrict the generalizability of the present findings.